2017
DOI: 10.1097/ncq.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Altered Medication Administration Time on Interdisciplinary Bedside Rounds on Academic Medical Ward

Abstract: Interdisciplinary rounds provide a valuable venue for delivering patient-centered care but are difficult to implement due to time constraints and coordination challenges. In this article, we describe a unique model for fostering a culture of bedside interdisciplinary rounds through adjustment of the morning medication administration time, auditing physician communication with nurses, and displaying physician performance in public areas. Implementation of this model led to measurable improvements in physician-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…25 Organizational complexity contributed to workflow differences that were a formidable barrier to inter-professional participation and thus communication during patient care rounds. Similar to findings by others, 17,26 this study found disconnected physician and nurse workflows, which have been characterized as "parallel play," 27 where individuals work alongside but do not interact with one another. Some studies have found that strategies such as localizing or regionalizing physicians to specific units may be a way to facilitate more interactions between physicians and nurses, 6,28 and improve nurse presence at rounds while decreasing mean rounding time.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…25 Organizational complexity contributed to workflow differences that were a formidable barrier to inter-professional participation and thus communication during patient care rounds. Similar to findings by others, 17,26 this study found disconnected physician and nurse workflows, which have been characterized as "parallel play," 27 where individuals work alongside but do not interact with one another. Some studies have found that strategies such as localizing or regionalizing physicians to specific units may be a way to facilitate more interactions between physicians and nurses, 6,28 and improve nurse presence at rounds while decreasing mean rounding time.…”
Section: Discussionsupporting
confidence: 86%
“…We also found however that some nurses did not feel welcomed by physicians during rounds, with the result that nurses either did not go to rounds or were mostly passive participants. One study conducted audits of the number of physician calls inviting nurses to rounds, and publicly displayed a graph of the frequency with which physicians called nurses for rounds, 17 which was successful in changing physician behavior. The effect of interpersonal relationships on communication has been reported by others, 31,32 and indeed, communication has been defined as the development of shared understanding by building and maintaining relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many of the respondents suggested that changing the time of the rounding practice itself may be most helpful, other strategies reported in the literature include adjusting other work typically performed during the same time. For example, altering medication administration times from 9:00 a.m.-7:00 a.m. helped foster greater communication and teamwork climate during IDR (Young et al, 2016). It is important for hospital units to assess the competing demands on staff that may prevent attendance at IDR.…”
Section: Organisational Factors Influencing Interdisciplinary Rounding Practicesmentioning
confidence: 99%
“…Nurses historically participated in rounding with physicians in a supportive role, rather than as a participant in shared decision-making (Beaird, 2019). Other barriers include that rounding commonly occurs during the morning hours thus coinciding with morning medication administration and multiple other nursing care duties (Young et al, 2016). Similarly, all practitioners find themselves pulled in multiple directions at any point in the day.…”
Section: Introductionmentioning
confidence: 99%